2006
DOI: 10.1080/01411920600635494
|View full text |Cite
|
Sign up to set email alerts
|

Acoustical barriers in classrooms: the impact of noise on performance in the classroom

Abstract: There is general concern about the levels of noise that children are exposed to in classroom situations. The article reports the results of a study that explores the effects of typical classroom noise on the performance of primary school children on a series of literacy and speed tasks. One hundred and fifty-eight children in six Year 3 classes participated in the study. Classes were randomly assigned to one of three noise conditions. Two noise conditions were chosen to reflect levels of exposure experienced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
167
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(181 citation statements)
references
References 28 publications
9
167
1
4
Order By: Relevance
“…In addition teachers indicate they have to speak at a level that strains their voices and results in throat diseases. Research has proved that good room acoustics reduces the teacher's stress level [1][2][3]. The problem of poor acoustics increases in rooms for learning and teaching foreign languages and disabled people.…”
Section: Introductionmentioning
confidence: 99%
“…In addition teachers indicate they have to speak at a level that strains their voices and results in throat diseases. Research has proved that good room acoustics reduces the teacher's stress level [1][2][3]. The problem of poor acoustics increases in rooms for learning and teaching foreign languages and disabled people.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the physical characteristics of classrooms are one of many contributing factors that may impact elementary student learning (Lanham, 1999). Specifically, higher background noise levels (BNL) have been found to be significantly correlated to lower student achievement scores both in occupied classrooms (Dockrell and Shield, 2006;Shield and Dockrell, 2008) and unoccupied ones (Ronsse and Wang, 2010). Since it is more straightforward to design buildings to meet unoccupied BNL guidelines, this paper presents a more comprehensive study on how unoccupied BNL is correlated to student learning, removing some limitations of the Ronsse and Wang (2010) study.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that noise and light in classrooms is one of many issues that may hamper sound education (Dockrell & Shield, 2006). The findings of this study showed that extraneous sound and light have an impact on learning.…”
Section: Significance Of the Studymentioning
confidence: 49%
“…This study examined the impact of eliminating extraneous sound and light on student achievement. As noted earlier, neuroscience and cognitive psychology literature on the effect of sound and light on cognition and studies on the impact of sound on learning (Andrews, 1990;Bess et al, 1998;DiSarno et al, 2002;Dunn, 1990;Dunn & Griggs, 1990;Gadwa & Griggs, 1985;Kreisman, & Crandell, 2002) have indicated that in the typical classroom (Bronzaft & McCarthy, 1975;Evans & Maxwell, 1975;Maxwell & Evans,2000), various environmental and studentrelated factors interfere with listening and comprehending (Dockrell & Shield, 2006;Flexer, 2009). …”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation